Comparative Analysis of Gut Microbiota Changes in Père David's Deer Populations in Beijing Milu Park and Shishou, Hubei Province in China - Zhang, Meishan; Shi, Minghui; Fan, Mengyuan; Xu, Shanghua; Li, Yimeng; Zhang, Tianxiang; Cha, Muha; Liu, Yang; Guo, Xiaobing; Chen, Qi; Li, Yiping; Zhang, Shumiao; et al. (Frontiers in Microbiology, 2018)
This study used 16S rRNA high-throughput sequencing technology to examine the differences in gut microbiota between the Père David’s deer populations in the Beijing and Shishou areas of China in order to understand the effects of ex situ conservation on the intestinal microflora in the Père David’s deer. Results: On the phylum level, the main bacteria found in the Père David’s deer populations from both areas were similar: Firmicutes and Bacteroidetes. However, the relative abundances of the two groups were significantly different. Alpha diversity results indicated that there was a difference in the evenness of the microflora between the two groups, and the beta diversity results further indicated that there was a significant difference in the microflora structure between the two groups. Conclusions: During the ex situ conservation process of the Père David’s deer, their food sources may change, resulting in differences in the gut microbiota. The intestinal microflora in the Père David’s deer from the same area are clustered. Therefore, the impact of changes in food on the gut microbiota of the Père David’s deer should be taken into consideration during ex situ conservation.